Risk of falls in the rheumatic patient at geriatric age - Agnieszka Prusinowska; Arkadiusz Komorowski; Teresa Sadura-Sieklucka; Krystyna Księżopolska-Orłowska (Rheumatology, 2017)
Evaluating the risk of falling of a geriatric rheumatic patient plays an essential role not only in planning and carrying out the physiotherapeutic process. The consequences of falls may be different and, although they do not always result in serious repercussions such as fractures or injuries, it is sufficient that they generate the fear of falling and cause a significant reduction in physical activity. Assessing functional capacity to define the risk of falling is of utmost importance in the case of patients after joint arthroplasty surgeries. The specificity of rheumatic patient’s falls is determined by numerous factors. It is not always possible to avoid them. However, it becomes vital to include fall prevention in the rehabilitation process as well as to prepare the house for the needs of an elderly person so that they are safe and as self-dependent as possible.